1990
DOI: 10.1111/j.1471-4159.1990.tb08817.x
|View full text |Cite
|
Sign up to set email alerts
|

Both A1 and A2a Purine Receptors Regulate Striatal Acetylcholine Release

Abstract: The receptors responsible for the adenosine-mediated control of acetylcholine release from immunoaffinity-purified rat striatal cholinergic nerve terminals have been characterized. The relative affinities of three analogues for the inhibitory receptor were (R)-phenylisopropyladenosine greater than cyclohexyladenosine greater than N-ethylcarboxamidoadenosine (NECA), with binding being dependent of the presence of Mg2+ and inhibited by 5'-guanylylimidodiphosphate [Gpp(NH)p] and adenosine receptor antagonists. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
3
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 46 publications
8
80
3
1
Order By: Relevance
“…13 -32 These observations have suggested that adenosine has a "universal" depressor effect in the CNS. However, our present results in the NTS (which are the first to demonstrate an increase in glutamate release by adenosine) and studies by others documenting an increase of dopamine 49 and acetylcholine 50 by purines, seriously challenge this concept and indicate that regional brain differences are present. In these last two reports, it was shown that activation of the adenosine receptor subtype A^ increases the release of striatal dopamine 49 or acetylcholine.…”
Section: -45contrasting
confidence: 47%
“…13 -32 These observations have suggested that adenosine has a "universal" depressor effect in the CNS. However, our present results in the NTS (which are the first to demonstrate an increase in glutamate release by adenosine) and studies by others documenting an increase of dopamine 49 and acetylcholine 50 by purines, seriously challenge this concept and indicate that regional brain differences are present. In these last two reports, it was shown that activation of the adenosine receptor subtype A^ increases the release of striatal dopamine 49 or acetylcholine.…”
Section: -45contrasting
confidence: 47%
“…Nonetheless, adenosine anaiogs inhibit central release of acetylcholine (8,17,36) and cholinergic agonists and antagonists have effects on locomotor activity (3,18,30,33). Therefore, both nicotinic and muscarinic agents were investigated in control and caffeinetreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the "synergistic" hypothesis can not explain the inhibitory effects exerted by certain doses of an A 2A receptor agonist on both D 1 -and D 2 -induced turning (Morelli et al 1994). Since adenosine A 2A receptors modulate acetylcholine (Brown et al 1990), GABA (Ferré et al 1993) and glutamate release (Popoli et al 1995), other indirect mechanisms may also account for the A 2A /D 1 interaction.…”
Section: Influence Of Sch 58261 On D 1 -And D 2 -Dependent Turning Bementioning
confidence: 99%
“…Moreover, the "synergistic" hypothesis can not explain the inhibitory effects exerted by certain doses of an A 2A receptor agonist on both D 1 -and D 2 -induced turning (Morelli et al 1994). Since adenosine A 2A receptors modulate acetylcholine (Brown et al 1990), GABA (Ferré et al 1993) and glutamate release (Popoli et al 1995), other indirect mechanisms may also account for the A 2A /D 1 interaction.As for the ability of SCH58261 to selectively potentiate D 2 -dependent rotations, this finding is in line with a previous study showing that CGS 21680, an adenosine A 2A receptor agonist, antagonized quinpirole-but not SKF 38393-induced turning in 6-OHDA-lesioned rats (Ferré et al 1999). Taken together, these results provide a behavioral support for the view that a specific antagonistic interaction exists between adenosine A 2 and dopamine D 2 receptors in the neostriatum (Ferré et al 1991b), an interaction which was found to be even increased in 6-OHDA-lesioned rats .…”
mentioning
confidence: 99%